2016
DOI: 10.1021/acs.jpcc.6b08471
|View full text |Cite
|
Sign up to set email alerts
|

Role of Intrinsic Photogeneration in Single Layer and Bilayer Solar Cells with C60 and PCBM

Abstract: In an endeavor to examine how optical excitation of C60 and PCBM contribute to the photogeneration of charge carriers in organic solar cells, we investigated stationary photogeneration in single-layer C60 and PCBM films over a broad spectrum as a function of the electric field. We find that intrinsic photogeneration starts at a photon energy of about 2.25 eV, i.e., about 0.4 eV above the first singlet excited state. It originates from charge transfer type states that can autoionize before relaxing to the lower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
66
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 39 publications
(84 citation statements)
references
References 64 publications
18
66
0
Order By: Relevance
“…Indeed, time-dependent density functional theory (TD-DFT) calculations on the PIPCP Frenkel exciton and the CT state at the interface with PC 61 BM show that for certain PIPCP/PC 61 BM molecular configurations the E CT is higher in energy than the PIPCP S 1 . [43] Importantly, however, charge generation in PIPCP:PC 61 BM is not field dependent (Figure 3a), and the field dependence of the photocurrent which is observed in the EQE spectra does not appear to depend on excitation wavelength, until excitation energies where the fullerene may be directly excited [46] (Figure 3b, Figure S4b,c, Supporting Information). The temperature dependence of the EQE spectra may also be interpreted as resulting from "hot-generation," where electronic excess energy from exciting to S n>1 can assist in charge generation.…”
Section: Temperature-dependent Photocurrentmentioning
confidence: 99%
“…Indeed, time-dependent density functional theory (TD-DFT) calculations on the PIPCP Frenkel exciton and the CT state at the interface with PC 61 BM show that for certain PIPCP/PC 61 BM molecular configurations the E CT is higher in energy than the PIPCP S 1 . [43] Importantly, however, charge generation in PIPCP:PC 61 BM is not field dependent (Figure 3a), and the field dependence of the photocurrent which is observed in the EQE spectra does not appear to depend on excitation wavelength, until excitation energies where the fullerene may be directly excited [46] (Figure 3b, Figure S4b,c, Supporting Information). The temperature dependence of the EQE spectra may also be interpreted as resulting from "hot-generation," where electronic excess energy from exciting to S n>1 can assist in charge generation.…”
Section: Temperature-dependent Photocurrentmentioning
confidence: 99%
“…[1] Although fullerenes have been used widely in OPV devices, their (photo)excited state properties have received relatively little attention up to now. [2,[7][8][9][10] In fact, these studies suggest that fullerenes not only play a role as electron acceptor, but also can contribute significantly to light harvesting in the photoactive layer. [2,[7][8][9][10] In fact, these studies suggest that fullerenes not only play a role as electron acceptor, but also can contribute significantly to light harvesting in the photoactive layer.…”
Section: Doi: 101002/aenm201802476mentioning
confidence: 99%
“…[2][3][4][5][6] However, the role of fullerenes as light absorber contributing to the photocurrent generation has gained increasing recognition as several recent reports demonstrate. [2,3,[6][7][8]11] For instance, Burkhard et al showed that free charge carriers can be generated upon light absorption by fullerenes. [2,3,[6][7][8]11] For instance, Burkhard et al showed that free charge carriers can be generated upon light absorption by fullerenes.…”
Section: Doi: 101002/aenm201802476mentioning
confidence: 99%
See 2 more Smart Citations